Marginalized Males, Disparate COVID-19 Outcomes, and Health Equity: A Profile of Highest Risk - Tyler Barnhart MPH (SAGE Publishing, 2021)
This paper is a direct response to Smith et al.’s (2020) call for more insight into health equity concerns pertaining to COVID-19 outcomes. The goal of this discussion is to offer the field with an evidence-informed ‘avatar’ representing the most-impacted group as it pertains to COVID-19 mortality and morbidity. Policy and practice implications are offered as a call to action for public health professionals to support these most impacted and highest risk communities.